2017
DOI: 10.1108/ijcthr-11-2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

The influences of cleanliness and employee attributes on perceived service quality in restaurants in a developing country

Abstract: Page 21 of 56International Journal of Culture, Tourism, and Hospitality Research 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 87 publications
(138 reference statements)
3
29
0
1
Order By: Relevance
“…Researchers have shown in many contexts the relationship between perceived service quality and willingness to use a service. Recent examples of these contexts include air travel (Hussain et al 2015), government e-services (Sharma 2015), restaurants (Truong et al 2017), and service innovations (Storey et al 2016). The current study is interested in these relationships not as an attempt to replicate those prior studies, but rather to link the expected effects we noted earlier.…”
Section: Mediation Of Reputationmentioning
confidence: 78%
See 1 more Smart Citation
“…Researchers have shown in many contexts the relationship between perceived service quality and willingness to use a service. Recent examples of these contexts include air travel (Hussain et al 2015), government e-services (Sharma 2015), restaurants (Truong et al 2017), and service innovations (Storey et al 2016). The current study is interested in these relationships not as an attempt to replicate those prior studies, but rather to link the expected effects we noted earlier.…”
Section: Mediation Of Reputationmentioning
confidence: 78%
“…In this respect, perceived service quality functions as a signal, which sellers and the marketplace develop. Truong et al (2017) found the perceived quality of food, atmosphere, cleanliness, and employees affected the perceived service quality of a restaurant. Ho and Wei (2016) found authentic experiences with sellers affect perceived service quality, which they described as a function of signal credibility.…”
Section: Perceived Service Qualitymentioning
confidence: 98%
“…Berry et al (2006) classified the service attributes into three groups which are Mechanic Clues, Humanic Clues and Functional Clues. First, Mechanic Clues consist of the sensory presentation of the service; for instance, ambience, scent, light, touch, taste and sound (Berry et al 2006;Chua et al 2014;Truong et al 2017). Second, Humanic Clues consist of the appearance and behaviour of service staff, who directly interact with and deliver the service values to customers (Berry et al 2006).…”
Section: Innovative Service Cluesmentioning
confidence: 99%
“…Service staff is considered as one of the key players that influence customer impression of the service performance. Humanic Clues are determinants that have always been a concern to scholars in the hospitality field to maximise the positive experience for customers (Chua et al 2014;Nguyen et al 2014;Garg and Amelia 2016;Truong et al 2017). Third, Functional Clues are those that deliver the efficiency and accuracy of the technical quality at its presence or absence (Berry et al 2006).…”
Section: Innovative Service Cluesmentioning
confidence: 99%
“…& Patton, 1995;Markovic, Komsic, & Stifanic, 2013). Using this instrument, validation of the dimensions of DINESERV has been evaluated in different countries such as Korea (Kim, McCahon & Miller, 2003), Croatia (Marković, Raspor & Šegarić, 2010), Malaysia (Bougoure & Neu, 2010), Jordan (Ala'a, Ahmad, & Ahmad, 2015) Sudan (Diab, Mohammed, Mansour, & Saad, 2015) and some western countries and cities such as London (Mhlanga, Hattingh, & Moolman, 2014), England (Truong, Nisar, Knox, & Prabhakar, 2017), Turkey (Murat & Memis, 2017) and in the capital cities of Europe (Radojevic, Stanisic, Stanic, & Sarac, 2014). Overall, the research findings from these studies indicate that DINESERV is a valid tool in different cultures, and the quality of service may differ considerably according to guests' and food service outlets' characteristics.…”
Section: Measuring Service Qualitymentioning
confidence: 99%